The Development of Social Brain Functions in Infancy. - Grossmann, Tobias (Psychological Bulletin, 2015)
One fundamental question in psychology is what makes humans such intensely social beings. Probing the developmental and neural origins of our social capacities is a way of addressing this question. In the last 10 years the field of social-cognitive development has witnessed a surge in studies using neuroscience methods to elucidate the development of social information processing during infancy. While the use of electroencephalography (EEG)/event-related brain potentials (ERPs) and functional near-infrared spec-troscopy (fNIRS) has revealed a great deal about the timing and localization of the cortical processes involved in early social cognition, the principles underpinning the early development of social brain functioning remain largely unexplored. Here I provide a framework that delineates the essential processes implicated in the early development of the social brain. In particular, I argue that the development of social brain functions in infancy is characterized by the following key principles: (a) self-relevance, (b) joint engagement, (c) predictability, (d) categorization, (e) discrimination, and (f) integration. For all of the proposed principles, I provide empirical examples to illustrate when in infancy they emerge. Moreover, I discuss to what extent they are in fact specifically social in nature or share properties with more domain-general developmental principles. Taken together, this article provides a conceptual integration of the existing EEG/ERPs and fNIRS work on infant social brain function and thereby offers the basis for a principle-based approach to studying the neural correlates of early social cognition.